IMPLEMENTASI KEBIJAKAN PENDIDIKAN KARAKTER DI SMP NEGERI 5 MATARAM TAHUN PELAJARAN 2019/2020 - Najwa, Lu`luin; Najah, Pajriatun; Hardiansyah, Hardiansyah (Universitas Pendidikan Mandalika, 2020)
This study aims to describe the implementation of education character policy at SMP Negeri 5 Mataram, the proponent and the resistor factors, and the effect of education character policy implementation on students. This research used a descriptive qualitative approach. The subject of this study involved: the principal, the student head deputy, the homeroom teacher, the religion teacher, and the counseling teacher. The observation, interview, and documentation are used as data collection methods. Furthermore, the result of this study showed that (1) the implementation of education character policy at SMP Negeri 5 Mataram was implemented by school residents with teaching and learning activities.(2) the proponent factors were an internal factor (student awareness) and an external factor (the cooperation among teachers, employees, conducive neighborhood, and programmed activities). (3) the resistor factors were an internal factor (the student character diversity, the teacher limitedness on education character implementation), the external factor was (the lack of parent supervision on problematic children). (4) The effect of education on character implementation creates self-confidence and discipline.Â Keywords:Implementation, education character policy